Survival rate of colorectal cancer in China: A systematic review and meta-analysis - Wang, Ren; Lian, Jie; Wang, Xin; Pang, Xiangyi; Xu, Benjie; Tang, Shuli; Shao, Jiayue; Lu, Haibo (Frontiers in Oncology, 2023)
Background This study aims to comprehensively summarize the colorectal survival rate in China. Method: In PubMed and Web of Science, keywords such as “colorectal cancer”, “survival” and “China” were used to search literatures in the past 10 years. Random effect models were selected to summarize 1-year, 3-year, and 5-year survival rates, and meta-regression and subgroup analyses were performed on the included studies. Results A total of 16 retrospective and prospective studies providing survival rates for colorectal cancer in China were included. The 1-year, 3-year, and 5-year survival rates of colorectal cancer in China were 0.79, 0.72 and 0.62, respectively. In the included studies, the 5-year survival rates of stage I (5474 cases), stage II (9215 cases), stage III (8048 cases), and stage IV (4199 cases) colorectal cancer patients were 0.85, 0.81, 0.57 and 0.30, respectively. Among them, the 5-year survival rates of colorectal cancer were 0.82, 0.76, 0.71, 0.67, 0.66, 0.65 and 0.63 in Tianjin, Beijing, Guangdong, Shandong, Liaoning, Zhejiang and Shanghai, respectively. Conclusion The 5-year survival rate in China is close to that of most European countries, but still lower than Japan and South Korea, and the gap is gradually narrowing. Region, stage, differentiation, pathological type, and surgical approach can affect 5-year survival in colorectal cancer. Systematic review registration https://www.crd.york.ac.uk/prospero/ identifier, CRD42022357789.